Evaluation of the conformity of assistential practice in the maintenance of the temporary double-lumen dialysis catheter - Rosetti, Késia Alves Gomes (Rev Lat Am Enfermagem, 2014)
OBJECTIVE: to evaluate the conformity of the assistential practice in the maintenance of the temporary double-lumen catheter for hemodialysis, by means of the use of the process indicator, in the University Hospital of the University of São Paulo. METHOD: a quantitative, exploratory-descriptive and observational study. The sample was made up of 155 observations of persons with temporary double-lumen catheters, in the period March - November 2011, using the Indicator of the Maintenance of the Temporary Double Lumen Catheter for Hemodialysis. RESULTS: the rate of general conformity of the assistential practice corresponded to 65.8%. Of the practice's 13 components, 9 (69.2%) attained 100% conformity. The hygienization of hands by the professionals and the use of a mask by the patients during the disconnection from the hemodialysis had the worst rates (83.9%). CONCLUSION: although the actions evaluated are implemented in the unit, it is necessary to propose and apply educational strategies with the health team, as well as to institute periodical assessments, so as to raise the conformity rates, ensuring the quality of the hemodialysis services.